2017
DOI: 10.1002/jor.23664
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral quadriceps and hamstrings muscle volume asymmetries in healthy individuals

Abstract: Determining the magnitude of quadriceps and hamstring muscle volume asymmetries in healthy individuals is a critical first step toward interpreting asymmetries as compensatory or abnormal in pathological populations. The purpose of this study was to determine the magnitude of whole and individual muscle volume asymmetries, quantified as right-left volume differences, for the quadriceps and hamstring muscles in a young and healthy population. Twenty-one healthy individuals participated: Eleven females age = 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Bilateral comparison is important for deciding the return to activity after ACLR. Many studies have reported that less than 15% bilateral differences in knee extension strength could be a proper standard for the return to activity [ 14 , 15 , 16 ]. Additionally, various studies have suggested the bilateral comparison of the functional performance limb symmetry index (LSI), such as the hop-test LSI, as a decision-making assessment for the return to activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral comparison is important for deciding the return to activity after ACLR. Many studies have reported that less than 15% bilateral differences in knee extension strength could be a proper standard for the return to activity [ 14 , 15 , 16 ]. Additionally, various studies have suggested the bilateral comparison of the functional performance limb symmetry index (LSI), such as the hop-test LSI, as a decision-making assessment for the return to activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were measured for height, mass, and their BMI calculated. They then underwent imaging of their dominant and nondominant thigh and knee using a 3‐T magnetic resonance image system (Trio; Siemens) using previously published techniques 29,30 . Knee scans were acquired first with a 15‐channel knee coil (Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…Some degree of interlimb asymmetries in hamstrings strength is the norm ( Boccia et al, 2018 ; Kulas et al, 2018 ; Cuthbert et al, 2021 ) and, if not excessive, are beneficial for performance of tasks involving change of direction and sprinting, without impaired jumping ( Coratella et al, 2018 ). Injured soccer players exhibit a more symmetrical recruitment pattern between ST, SM and BF (corresponding to a less economic hamstrings muscle activation), as opposed to the more asymmetric pattern of subjects without previous injuries ( Schuermans et al, 2014 ).…”
Section: Part 1: An Overview Of Hamstrings Injuriesmentioning
confidence: 99%